AN ECONOMIC ANALYSIS OF PRODUCTION, MARKETING AND VALUE CHAIN OF POTATO IN BAMYAN PROVINCE - Honaryar, Ghulam (International Journal of Research -GRANTHAALAYAH, 2019)
The present study on “An economic analysis of production, marketing and value chain of potato in Bamyan province” undertaken for studying the trend in production, productivity, marketing, value chain, cost of cultivation and problems faced by the farmers in production and marketing of potato. In Bamuan, potato is an important cash crop and source of income of agriculture production. Potato is emerged as an important vegetable crop for Yakowlang district of Bamyan province, with better productivity. Therefore, a study of economics of cultivation, marketing, value chain in Yakowlang district was undertaken. For this study, Yakowlang district and Bamyan center selected because of high level of production. In this study 126 farmers were selected from six villages, three for each district (Bamyan and Yakowlang). Relevant information was collected from the potato producer to know the economics of potato cultivation and analyzed according to various cost concept used in farm management studies. Cost of cultivation of potato calculated from the primary data collected from purposively selected grower of potato of Bamyan province. According to study, using gross margin analysis, net margin of farmers as average is around 134243 AFN per Hectare and according to production and yield of different potato varieties in Bamyan, Kabul and Panjsher provinces. Loura variety give highest yield in Bamyan province i.e. 65.37 Ton per Hectare and similarly in Kabul Amany Variety give highest yield that is 45.71 Ton per Hectare and finally Panjsher province is a major producer of potato in Afghanistan also Amany gives highest yield that is 51.67 Ton per Hectare. Similarly, marketable surplus of three different category of farmers, small farmers are around 88.4 percent, medium farmers were 92.68 percent and large farmers were around 90 percent had marketable surplus. Also major constraints with the farmers in potato production, and marketing ranked first was price instability, followed by high storage charges, uncertainty of water, inadequate marketing facility and spoilage of potato.